2013
DOI: 10.1172/jci71090
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate deficiency disrupts developmental angiogenesis and causes congenital diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) is a common birth malformation with a heterogeneous etiology. In this study, we report that ablation of the heparan sulfate biosynthetic enzyme NDST1 in murine endothelium (Ndst1 ECKO mice) disrupted vascular development in the diaphragm, which led to hypoxia as well as subsequent diaphragm hypoplasia and CDH. Intriguingly, the phenotypes displayed in Ndst1 ECKO mice resembled the developmental defects observed in slit homolog 3 (Slit3) knockout mice. Furthermore, introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 45 publications
(93 reference statements)
1
53
0
1
Order By: Relevance
“…SLIT3 is a secreted protein involved in cytoskeletal regulation, cell migration, and muscle patterning that uses heparan and/or chondroitin sulfatemodified PGs as cofactors and, depending on cellular context, can inhibit Wnt and SDF1/Cxcl12 signaling [35,40,41]. Transgenic deletion of Slit3 and heparan sulfate deficiency both produce congenital diaphragmatic hernia in mice [42,43], a phenotype associated with cryptorchidism in up to 30% of cases [21]. The existence of variably penetrant renal and ureteral anomalies in Slit À/À mice [43] suggests that the intermediate mesoderm is an important SLIT3 developmental target.…”
Section: Developmental Defects In Orl Cryptorchidismmentioning
confidence: 99%
“…SLIT3 is a secreted protein involved in cytoskeletal regulation, cell migration, and muscle patterning that uses heparan and/or chondroitin sulfatemodified PGs as cofactors and, depending on cellular context, can inhibit Wnt and SDF1/Cxcl12 signaling [35,40,41]. Transgenic deletion of Slit3 and heparan sulfate deficiency both produce congenital diaphragmatic hernia in mice [42,43], a phenotype associated with cryptorchidism in up to 30% of cases [21]. The existence of variably penetrant renal and ureteral anomalies in Slit À/À mice [43] suggests that the intermediate mesoderm is an important SLIT3 developmental target.…”
Section: Developmental Defects In Orl Cryptorchidismmentioning
confidence: 99%
“…In our previous studies, we have observed that endothelial Ndst1 deletion leads to reduced N-sulfation and 2-O and 6-O sulfation modifications of endothelial HS [15, 25, 26]. To verify the under sulfated status of the endothelial HS in the Ndst1 f/f Tie2Cre + animals, an FGF-2 binding assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The Ndst1 f/f Tie2Cre + mice were generated by breeding Ndst1 f/f mice with transgenic Tie2Cre mice as previously described [15, 26]. All experimental mice were fully backcrossed to C57BL/6 background and handled according to guidelines of the University of Georgia Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How this binding affects the complex spatial biology of the ECM is poorly understood, especially given the diverse array of differentially expressed HSPGs, and the variable composition of their HS chains [20]. One mechanism by which HSPGs modulate signaling pathways is by stabilizing gradients of signaling molecules, which provide spatial information to cells during development [24]. In angiogenesis, HSPGs establish a gradient of VEGF, which provides spatial context for the migrating endothelial cells which will form the blood vessel (Fig.…”
Section: Activities Of Hp/hsmentioning
confidence: 99%